A QM study on determination of vibrational frequencies of the surface coordinated species involved in CDRM - Karagöz, Burcu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2014)
The determination of the sites participating the reaction mechanism is of crucial importance in catalysis. Ni- and Co- based catalysts have been studied by our group for their activity in Catalytic Dry Reforming of Methane (CDRM). Although in-situ FTIRDRIFT tests have been conducted on those catalysts under adsorption and reaction conditions, and the vibrational spectra were obtained, the available information in the literature is not detailed and surface specific enough to allow the determination of the active sites on the catalyst. The aim of this study is to obtain a vibrational frequency database for the species involved in CDRM reaction mechanism occurs on the possible active faces of the Co- and Ni- based catalysts. In the formation of the database, quantum mechanical simulations utilizing Density Functional Theory (DFT) calculations are used. In the simulations, the metallic faces whose presences have been confirmed for our CDRM catalysts by XRD were considered. Vibrational frequencies of CHx(x=0-4), CO2, CO, O and H on Co(111) flat surface, Ni(220) and NiPt(220) terraced surfaces were calculated for each possible sites via DMol3 tool of Accelrys Materials Studio. Calculated vibrational frequencies of CO2, CO, CH3, and CH2 on Co(111) are in good agreement with the literature. Adsorption energies of CO2, CO, O, CH4, CH3, and CH2 on Co(111) are inversely related with their stretching frequencies whereas there is a linear relationship for adsorbed CH, C, and H on Co(111). Furthermore, calculated vibrational frequencies of CO2, CO and CH2 on Ni(220) are consistent with the literature, while stretching frequency of CH3 is far different from experimental findings, due to possible alloy formation, and geometry and/or support effect. Comparative analysis of the results obtained for Ni(220) and NiPt(220) revealed that for NiPt(220) surface, Pt existence affect the vibrational frequencies of all species. Moreover, CO2 and CO vibrational frequencies on NiPt(220) are considerably close to experimental findings. Vibrational frequency of CH4 is inconsistent with the literature for all surfaces, most probably because the weak CH4 adsorption on these surfaces may not be precisely calculated by DFT.
Keywords: Carbon dioxide mitigation.; Methane.; Catalysts.